Saniya Saleh: Her Poetry and Originality - Lotfiyya Ibrahim Barham (دراسات في اللغة العربيّة وآدابها)
This research is on exploration of Saniya Saleh's poetry. It tries to specify its literary position and the significance of its originality. Although this article emphasizes that this poetess follow the modernist movement in Arabic poetry, it by no means posits her Poetry in contrast with the traditional Arabic Poetry, which enjoys meters and rhymes. In fact, this article maintains that Saniya Saleh's poetry has been able to resist the innovations emerging in modern Arabic poetry. This has been discussed along two trajectories in order to illustrate the stylistic features of this poetess: 1. defamiliarization and 2. transcending religious beliefs.